PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KEPUASAN KERJA RS MARTHA FRISKA - Novien Rialdy; Irwan Syari Tanjung; Willy Yusnandar (POLITEKNIK LP3I JAKARTA, 2025)
Competence is a basic characteristic possessed by someone who has direct influence to predict the performance of a company's employees. Competence is needed to improve the quality of human resources in the company. In addition to competence, training can also influence the progress of the company. A company needs to provide training to employees. The objective of the study is to test and analyze the effects of competence and training on employee performance at Martha Friska Hospital Medan. The research data were analyzed by using multiple linear regression analysis. The research populations were 212 employees while the research samples were 138 respondents. The result of the study shows that competence and training simultaneously have a significant effect on employee job satisfaction.